Digital transformation of grades-related technologies at Dr. Jose P. Rizal Senior High School (2020–2024): A case study on usability and impact - Casas, Paul Enrique C.; Barrameda, Maria Lalaine M.; Elarmo, Jessa Mae C.; Rodriguez, Danielle Jana Roe P.; Prestado, Jessa Mae D. (CV. Yudhistt Fateeh, 2025)
This participatory case study examines the digital transformation of grades-related enabling technologies at Dr. Jose P. Rizal Senior High School from 2020 to 2024. Grounded in principles of sociotechnical theory and the Technology Acceptance Model (TAM), the study defines enabling technologies as digital solutions that enhance educational processes. It traces the institution's transition from manual procedures to a macro-enabled MS Excel eTool, and finally to the centralized Students Enrollment and Records Management System (SERMS). Using a mixed-methods approach that integrated historical document analysis, stakeholder feedback, and usability assessments, the research documented a four-phase progression from individual initiatives to institution-wide adoption. Findings indicate that strategic leadership, stakeholder collaboration, and user-centered design were pivotal to successful integration. Usability evaluation, based on the System Usability Scale and qualitative feedback from 31 faculty members, showed a statistically significant improvement from